Triple Batch Digesters in Series Method to Analyze Biogas Potential from Bioethanol Vinasse - Syaichurrozi, Iqbal; Budiyono, Budiyono; Sumardiono, Siswo (World Chemical Engineering Journal, 2015)
The purpose of this study was to investigate biogas production from bioethanol vinasse using the simple method which was triple batch digester in series mode. Three digesters (A, B, C) were used in laboratory scale and carried out in 30 days respectively. The fresh rumen was added in substrates before that were put into each digester (A, B, C). Ratio of COD/N in substrat was adjusted in variation of 1436/7, 400/7, 500/7, 600/7, 700/7. The results showed that in digester A, biogas was produced in large amount a first time of fermentation. In digester B, biogas generated was less than that in digester A. Meanwhile, in digester C, biogas was not produced again. Ratio of 500/7 and 600/7 generated the most biogas volume which was 9,322 and 9,168 mL. Keywords: Bioethanol, Biogas, Series Method, Triple Batch, Vinasse,